PENGARUH KEPEMILIKAN KELUARGA, LIKUIDITAS DAN LEVERAGE TERHADAP MANAJEMEN LABA: (Studi Empiris pada Perusahaan Pertambangan yang terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Putri, Fadiyah Ramadhani; Mulyani, Erly (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to examine the effect of Family Ownership, Liquidity, and Leverage on Earnings Management Methods: The sample was selected using purposive sampling, resulting in 120 observations from 40 mining companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. Hypothesis testing was conducted using multiple linear regression, with data processed in SPSS.Results: This study indicates that family ownership, liquidity, and leverage have both negative and positive effects on earnings management.Conclusion and suggestion: This study concludes that, overall, ownership structure and a company’s financial condition play important roles in shaping earnings management practices in mining companies. As a result, companies are advised to strengthen internal control mechanisms and maintain sound financial management to minimize earnings management practices. Keywords: Earnings Management, Family Ownership, Leverage, Liquidity